2010
DOI: 10.1007/s10533-010-9531-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus cycling in a small watershed in the Brazilian Cerrado: impacts of frequent burning

Abstract: Plant productivity in many tropical savannas is phosphorus limited. The biogeochemical cycling of P in these ecosystems, however, has not been well quantified. In the present study, we characterized P stocks and fluxes in a well-preserved small watershed in the Brazilian Cerrado. As the Cerrado is also a firedominated ecosystem, we measured the P stocks and fluxes in a cerrado stricto sensu plot with complete exclusion of fire for 26 years (unburned plot) and then tested some predictions about the impacts of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 36 publications
4
34
0
11
Order By: Relevance
“…Este domínio ocupa cerca de 24% do território brasileiro, cobrindo aproximadamente 200 milhões de hectares e possui a segunda maior biodiversidade do planeta (BUSTAMANTE et al, 2006) Inúmeros estudos foram desenvolvidos neste domínio, sendo verificados, em maior proporção, pesquisas sobre a dinâmica dos elementos carbono e nitrogênio (BUSTAMANTE et al, 2006;SIQUEIRA NETO;BERNOUX, 2008;CARVALHO et al, 2010;COSTA JUNIOR et al, 2011;LOSS et al, 2012a) comparativamente ao fósforo (P) e ao seu fracionamento. Sobre a dinâmica do P, em solos do Cerrado são encontrados trabalhos com ênfase somente na vegetação natural de Cerrado (RESENDE et al, 2011;BUSTAMANTE et al, 2012) e trabalhos comparando diferentes sistemas de uso das terras com a vegetação original (Cerrado) (FONTANA et al, 2008;EBERHARDT et al, 2008;TIRLONI et al, 2009;PEREIRA et al, 2010;LOSS et al, 2012a).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Este domínio ocupa cerca de 24% do território brasileiro, cobrindo aproximadamente 200 milhões de hectares e possui a segunda maior biodiversidade do planeta (BUSTAMANTE et al, 2006) Inúmeros estudos foram desenvolvidos neste domínio, sendo verificados, em maior proporção, pesquisas sobre a dinâmica dos elementos carbono e nitrogênio (BUSTAMANTE et al, 2006;SIQUEIRA NETO;BERNOUX, 2008;CARVALHO et al, 2010;COSTA JUNIOR et al, 2011;LOSS et al, 2012a) comparativamente ao fósforo (P) e ao seu fracionamento. Sobre a dinâmica do P, em solos do Cerrado são encontrados trabalhos com ênfase somente na vegetação natural de Cerrado (RESENDE et al, 2011;BUSTAMANTE et al, 2012) e trabalhos comparando diferentes sistemas de uso das terras com a vegetação original (Cerrado) (FONTANA et al, 2008;EBERHARDT et al, 2008;TIRLONI et al, 2009;PEREIRA et al, 2010;LOSS et al, 2012a).…”
Section: Introductionunclassified
“…Em relação ao P, este é um elemento muito importante para o desenvolvimento dos vegetais (NOVAIS; SMYTH; NUNES, 2007;RESENDE et al, 2011). Entretanto, os solos tropicais, sendo grande parte destes encontrados no domínio morfoclimático do Cerrado, apresentam, normalmente, baixa concentração de P disponível e alto poder de "fixação" ou "retenção" do P via adubação SMYTH, 1999;EBERHARDT et al, 2008).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The dynamics of phosphorus (P) fractions, on the other hand, is much more complex and depend on various factors related to soil attributes, such as texture (Tokura et al, 2011), management system (Pereira et al, 2010;Bezerra et al, 2015), chemical and organic fertilization (TIRLONI et al, 2009;GUARDINI et al, 2012;BEUTLER et al, 2015) and environmental (biotic and abiotic) factors (RESENDE et al, 2011). Agricultural systems such as CLI, which aims the maintenance of plant cover with minor soil tilling, can modify the dynamics of P fractions (BEZERRA et al, 2015;BEUTLER at al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The biogeochemical cycle of P is modified during vegetation and litter burning, by converting the organic P into orthophosphate (Certini, 2005), which is easily reactive with soils. Several studies have shown a relationship between vegetation burning and availability and quantities of P forms in soils (Giardina et al, 2000;Galang et al, 2010;Oliveira et al, 2011;Resende et al, 2011).…”
Section: Introductionmentioning
confidence: 99%